(untitled) (Swiss Medical Weekly, 2011)
During the 20th century Switzerland, like many other Western countries, experienced significant ageing of the population over the age of 65. As the lifespan of the Swiss population increases, so does the prevalence of falls. A multiplicity of fall prevention programmes are available, but extracting their most effective components remains a challenge. This article summarises the results of current studies on fall prevention, with a particular focus on methodological quality and successful reduction of fall incidence in vulnerable older people. Characteristics of effective fall prevention programmes in the fields of exercise, home modifications, appropriate footwear and walking aids are assessed. We then briefly discuss how these study results can be adapted to the Swiss context. This knowledge emphasises an interdisciplinary approach in the prevention of falls, the objective being to reinforce autonomy, promote health and enhance quality of life in vulnerable older people.